Determinants of Capital Structure: An Empirical Study on Cement Industry in Bangladesh - Mazumder, Manjurul Alam (Asian Accounting and Auditing Advancement, 2018)
The cement industry plays a vital role in the infrastructural development of Bangladesh. This industry requires huge funds to organize a business and further expand its capacity due to its capital intensity. The Capital structure of this industry shows unique features. The Debt ratio is taken to examine the impact of high or low the overall capital structure. The impact on the debt ratio is measured by five independent variables i.e., tangibility, profitability, size, growth, and tax. Spearman’s correlation coefficient, multiple regression model, and t-statistics are used as statistical tools. The result suggests that profitability and growth have a significant impact on the dependent variable (debt ratio) but they are negatively correlated, size, and tax has no significant impact on the debt ratio.